THU0484-HPR Role of "vial sharing" in achieving cost savings while using infliximab in rheumatology planned short stay unit. (23rd January 2014) - Singh, D.; Gupta, N.; Martin, K.; Mayhew, A.
Abstract : Background: In some clinical settings vial sharing is used after following local policies and appropriate strict clinical governance processes taking account of licensing, safety and good manufacturing practice. Although National Patient Safety Agency (NPSA) safety alerts does not support vial sharing but it has issued guidance on its use. Also, providing biologic therapy services in a unit like planned-short-stay-unit (PSSU) might aid in rationing a part of scarce resources; especially using "vial-sharing" when providing such therapies to patients en bloc in a unit. Objectives: We share our experience from a snapshot of our local workload on PSSU providing biologic therapies using principle of "vial-sharing" at our biologic unit in liaison with our pharmacy department. Methods: In this retrospective observational study, the active prescription charts for patients attending the PSSU at our Addenbrookes hospital, were obtained from pharmacy. Patients were at different stage of their treatment some on first initiation infliximab infusion and others on maintenance doses (range 1-51 with average 12.7 doses each). Data was lasting up to last 5years. The data for actual doses of infliximab given and "actual number of vials" (ANV) used were collected and exported to excel worksheets. The dose of infliximab is calculated as milligram per kg; hence the data for the "measured weight" documented in the prescription chart was also collected. Then, data was used to calculate the "expected number of vials" (ENV) which would have been used to deliver the same dose of infliximab with "no vial sharing". The data for the cost of the vials was obtained from pharmacy where cost of infliximab to Addenbrookes hospital inclusive of VAT per 100mg vial was £437.38 (confirmed with BNF). Subsequently the difference between ENV and ANV was used to depict the actual number of vials saved using "vial sharing" principle in our unit. From this difference and using the cost of a single vial an estimate of overall monitory savings was calculated, depicting total cost-savings from using "vial sharing". For example, for a 70kg man at 3mg/kg infliximab a single dose of 210 mg is prepared using 3 vials of 100 mg and 90mg discarded. Hence for 5 patients, it would need 15 vials to prepare individual dose; however, using vial sharing only 11 vials would be used saving 4 vials i.e. £1749.52 in monetary savings. Results: In total 65 patients were given infliximab therapy for an underlying rheumatological diagnosis over last 5 years and 827 infliximab infusion doses were dispensed by pharmacy. The costs were calculated for drug only and equipment and staffing costs were not included. Without vial sharing and using individual preparation using ENV, the cost of the treatment would have been £1, 085, 140. The actual cost of treatment calculated from ANV using "vial sharing" wherever possible was £985, 385. This led to estimated monetary savings of £99, 755. Conclusions: This observational analysis highlights the value of "vial sharing" in a set up where biologic therapies service can be delivered in a unit where preparing infusions for number of patients on the same day and using "vial sharing" can lead to significant monetary savings; perhaps can aid in creating more cost-effective pathways for future biologic-therapy-delivery-units. Disclosure of Interest: None Declared